Is Your Brain Strong Enough to Solve Hard Problems? : Brain Vitamins as a Simple Example for Multitasking Nanotechnology Scientis - Hendry Izaac Elim (SCIENCE NATURE, 2020)
As the number of world population reaches up to seven billion people, more complex problems will happen including broken living environmental system that is directly influenced the stress life of men. This systematic output is like the problem of aggregations and defects in material sciences identified well by physicists and nanotechnologist. As more and more smart questions are being ascended to fight against such negative impacts as well as unsolved problems in ongoing research works and its development, this paper presents a simple solution by showing a manner in such a way so that all the points of main problems and related obstacles can be guided in the truth way following by the salvation of many earthly people among the world complicated current problems and challenges. To simplify the answer and guidance for easy clarification, one took molecular electronics system (MES) of brain vitamins as the explanation for multitasking nanotechnology scientists who are in charge to carry out advanced research and its implementations in nanoscience and nanotechnology especially in exotics nanomaterials for smart nanochip fabrication. An integrated links among at least 3 different types and personalities of brain vitamins show a beautiful mind of their creator in nature of universe. The use of basic concept and principles of proposed electronic molecular system instead of mechanical or vibration system of molecules suggests that this technique is applicable for all various kind molecule structures. This idea of discovery of MES is very excellent to be applied to study many other healing system using different types of drugs.